2009
DOI: 10.1111/j.1442-2042.2009.02384.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral analgesia by non‐steroidal anti‐inflammatory drug zaltoprofen to manage cystoscopy‐related pain: A prospective study

Abstract: Objectives:To examine the pre-emptive analgesic effect of the non-steroidal anti-inflammatory drug zaltoprofen against rigid cystoscopy-associated pain, and compare it with the effect of an anesthetic gel. Methods: Forty men periodically undergoing follow-up office cystoscopy were enrolled in this prospective study. The effects of lidocaine gel alone or in combination with zaltoprofen, were examined. The following parameters were assessed using an 11-point numerical rating scale: pain during injection of gel i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…Komiya et al (10) suggested that combining premedication oral zaltoprofen (a non-steroidal anti-inflammatory drug) with intraurethral lidocaine with improved the cystoscopy-associated pain and provided a better quality of life for the patients. Calleary et al (11) proposed that the addition of nitrous oxide inhalation for men younger than 55 years who were undergoing flexible cystoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Komiya et al (10) suggested that combining premedication oral zaltoprofen (a non-steroidal anti-inflammatory drug) with intraurethral lidocaine with improved the cystoscopy-associated pain and provided a better quality of life for the patients. Calleary et al (11) proposed that the addition of nitrous oxide inhalation for men younger than 55 years who were undergoing flexible cystoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Lignocaine gel during this procedure has not been found to very effective. [12345] Zaltoprofen during check cystoscopy after transurethral resection (TUR) of bladder tumor (TURBT) has been proven to be more effective than lignocaine intraurethral analgesia. [5] Numerous reports exist on the effect of local anesthesia against cystoscopy-associated pain, but so far there has been no objective evaluation of the preemptive analgesic effect of nonsteroidal anti-inflammatory drugs (NSAIDs).…”
Section: Introductionmentioning
confidence: 99%
“…[12345] Zaltoprofen during check cystoscopy after transurethral resection (TUR) of bladder tumor (TURBT) has been proven to be more effective than lignocaine intraurethral analgesia. [5] Numerous reports exist on the effect of local anesthesia against cystoscopy-associated pain, but so far there has been no objective evaluation of the preemptive analgesic effect of nonsteroidal anti-inflammatory drugs (NSAIDs). [12] Hence, this study was undertaken to assess the effect of preemptive oral diclofenac in pain relief in patients undergoing DJ stent removal (DJSR) by rigid cystoscopy when compared to placebo and to assess the safety of oral diclofenac.…”
Section: Introductionmentioning
confidence: 99%
“…Lignocaine gel during this procedure is not very effective. [1], [2], [3], [4], [5] Numerous reports exist on the effect of local anesthesia against cystoscopy-associated pain, but so far there has been no study on the preemptive analgesic effect of nonsteroidal anti-inflammatory drugs (NSAIDs).…”
Section: Introductionmentioning
confidence: 99%